Why and when do citizens support populist right-wing social movements? Development and test of an integrative theoretical model. - Kleinert, Manuel; Schlueter, Elmar (Journal of Ethnic & Migration Studies, 2022)
What are the microlevel mechanisms that explain citizens' support of populist social movements? We address this question by focusing on the 'PEGIDA' (Patriotic Europeans against the Islamization of the Occident) protest groups in Germany, which became particularly prominent by attracting large numbers of attendees in street protests during the years 2015/16. We develop and test an integrative theoretical model that points to the key roles of anti-immigrant attitudes and political dissatisfaction as mediators linking subjective socioeconomic deprivation with citizens' support of the 'Pegida'-movement. Equally important, this model holds that citizens' political dissatisfaction moderates the nexus between anti-immigrant attitudes and support for 'Pegida'. The results based on data from seven cross-sectional general population surveys provide clear support for these predictions. Combined, these efforts help to advance scholarly understanding of not only why, but also how and under what conditions non-activist citizens support anti-immigrant collective action as exemplified by the 'Pegida' movement.